Effects of silk fibroin in murine dry eye - Kim, Chae Eun (Sci Rep, 2017)
The study aimed to investigate the effects of silk fibroin in a mouse model of dry eye. The experimental dry eye mouse model was developed using more than twelve-weeks-old NOD.B10.H2(b) mice exposing them to 30–40% ambient humidity and injecting them with scopolamine hydrobromide for 10 days. Tear production and corneal irregularity score were measured by the instillation of phosphate buffered saline or silk fibroin. Corneal detachment and conjunctival goblet cell density were observed by hematoxylin and eosin or periodic acid Schiff staining in the cornea or conjunctiva. The expression of inflammatory markers was detected by immunohistochemistry in the lacrimal gland. The silk group tear production was increased, and corneal smoothness was improved. The corneal epithelial cells and conjunctival goblet cells were recovered in the silk groups. The expression of inflammatory factors was inhibited in the lacrimal gland of the silk group. These results show that silk fibroin improved the cornea, conjunctiva, and lacrimal gland in the mouse model of dry eye. These findings suggest that silk fibroin has anti-inflammatory effects in the experimental models of dry eye.